Implementation Of Islamic Business Ethics In Clothing Stores: A Study In 16 Ilir Market Palembang - Hidayat, Rahmat; Delima, Putri; Sawalia, Nuris; Panorama, Maya (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze how Islamic business ethics are applied by Muslim fashion traders in Pasar 16 Ilir Palembang and its influence on consumer trust and loyalty. Methodology: The approach used is descriptive quantitative involving 55 respondents from the general public, students, and college students in Palembang. Data were collected using a Likert-based questionnaire that measures the application of the values of shiddiq (honesty), amanah (trust), tabligh (openness), and fathonah (wisdom). Results And Findings:  As many as 50.9% of respondents agreed and 38.1% strongly agreed that traders have implemented Islamic business ethics well. The shiddiq value obtained the highest score with 52 respondents giving a positive assessment, followed by amanah (50 respondents), fathonah (49), and tabligh (48). Novelty And Originality: This study offers a new contribution by focusing the study on the context of traditional markets, which have so far received less attention in Islamic business ethics studies, and emphasizing the application of local values in direct buying and selling practices. Conclusion:  The application of Islamic ethical principles has been proven to be able to build consumer trust and increase loyalty, which plays an important role in the sustainability of sharia-based businesses. Type of Paper:  Research paper.